TEKNOLOGI INFORMASI DAN PEMANFAATAN SISTEM INFORMASI KEUANGAN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA KOPERASI - Ghonimah Zumroatun Ainiyah; Kartika Dewi Permatasari; Siti Murwati (Program Studi Akuntansi, Universitas Kuningan, 2022)
The motivation behind this study was to decide informasi innovation and the utilization of monetary informasi frameworks on the adequacy of bookkeeping informasi frameworks in cooperatives, particularly in Purwareja Klampok and Mandiraja locale. This sort of exploration is quantitative examination by dispersing polls straightforwardly to supervisors and the money division of cooperatives in the two sub-regions. The number of inhabitants in this examination is the director and the money office upwards of 80 individuals. The example in this study was taken 80 individuals. The information examination procedure utilized various direct relapse. Quantitative examination in this review will utilize legitimacy and dependability tests with Cronbach's Alpha. Old style suspicion test incorporates ordinariness test, multicollinearity test and heteroscedasticity test. The outcomes show that informasi innovation and the utilization of monetary informasi frameworks have a huge and critical impact on bookkeeping informasi frameworks as confirmed by the consequences of the estimation of the SPSS application program, the R worth of the two factors is 0.806 while the coefficient of assurance is 0.650 (65%) implying that the level of the impact of informasi innovation factors and usage of monetary informasi frameworks by 65% and the excess 35% is affected by different factors that are excluded from this review.Keywords: Information Technology and Utilization of Financial Information Systems.